ELEMENTOS DA CULTURA DE INOVAÇÃO QUE FAVORECEM A ADOÇÃO DE PRÁTICAS DE ECOINOVAÇÃO: ANÁLISE DE EMPRESAS INDUSTRIAIS DO SETOR DA CONSTRUÇÃO - Vendler, Marize Helena da Rosa (2017)
The research is developed through the Evolutionary Theory, which considers a technological innovation as driving force behind the development of capitalist economies. In this sense, the research started from the assumptions that, for the companies obtain competitiveness, it is necessary a practices that integrates the objectives of innovation and of productive development, with a preservation of environment’s resources. To understand this assumption, a multi-case study was carried out with a general objective of analyzing the elements of the innovation culture that could favors the adoption of eco-innovation strategies in the construction industry as an organizational competitiveness’s factor. For this, the defined specific objectives were: To identify elements of the innovation culture in companies in the construction sector; To investigate the existence of eco-innovation practices in these companies; To analyze the managers' perception of the competitive capacity that results from the possible adoption of eco-innovation strategies; And to define indicators of practices for eco-innovations, through the identified cultural elements. These objectives were analyzed in five areas of the construction sector, in the Center-South (Guarapuava) and West (Cascavel) regions of State of Paraná, in Brazil. A methodological approach chosen was qualitative, through the multiple case study strategy. The instruments for data collection were semi-structured interviews, applied to a manager and a collaborator, who work on the environmental management of each company, totaling ten interviewees; Documentary analysis; Observation; And research diary. For the data analysis, it was used content analysis and triangulation. As main results of the research, they were found that elements of the innovation culture such as adaptability and flexibility, the environmental regulations and policies and market orientation, like the beliefs and values, the structure, the incentives to innovation and open communication, guide the development of environmental and innovative practices. In general, the elements of the innovation culture that most favor the adoption of eco-innovation practices in the companies studied are: "environmental regulations and policies" and "market orientation". These elements are influenced by sources of the external environment, which are seen as requirements that need to be fulfilled, but also enable the adoption of new products and procedures, which are used by companies to win customers. This consists that eco-innovation practices can conduct reactive strategies, related to the environmental impact caused by the productive activity of the construction sector and proactive strategies, which are seen as business opportunitie. From this perspective, it was observed that the companies’ managers studied understand that eco-innovation practices contribute to organizational competitiveness, since they guarantee the predilection of customers, mainly from those with certifications, and enable companies to be more successful than their competitors, by the showing of attributes of reduction of environmental impacts. This scenario confirms that the adoption of eco-innovation practices provides the achievement of results, such as the improvement of economic and productive performance, as well as to maintain and obtain competitive capacity. In this sense, it was verified that the research might be a strategic mechanism, since it offers an instrument of evaluation of indicators of eco-innovation practices, providing feedback to the managers. Thus, through this study companies can visualize how the elements of the innovation culture favor the adoption of eco-innovation strategies, and also realize what it needs to be developed in these elements, in order to create a culture of innovation with a more eco-innovative approach.